The Human Resource Development of Local Administrstion Organization :A Case study of Khonsawan district , Chaiyaphum province - Srichan, Thanikarn; Intaraprajob, Inthuraporn; Chanphong , Somsak; Photisuwanpanya , Thammarat; Phalapol, Chukiat (Journal of Modern Learning Development, 2021)
The aim of this research is 1) To study the development of human resources of local administrations. 2) examine the factors that influence the human resource development of the local government organization. 3) Study the problem and solution of developing the human resources of local authorities. Samples of this research are personnel from local government organizations in the Khonsawan district which is obtained by determining the size of the population from The formula for calculating the sample size using the Krejcie & Morgan table. The data collection tools are statistical questionnaires for data analysis using the program to calculate the percentage, mean, frequency distribution and standard deviation. The findings were summarized as follow: 1.The results from personal factors information of local government organization staffs in Khonsawan district. The majority of the samples are female (61.54%) and male (38.46%) and are between 36 and 45 years old. 73.93% completed bachelor degrees. 53.42% earn monthly income 10,000-20,000 bath. 68.80% staffs are married. Time period in performance at organization is period between 6-10 years (39.32%). 2. The factors affecting human resource development of the local government organization were found to have five factors, namely 1) the determination of human resource management guidelines. Including budget allocation in the organization. 2) Factors related to training needs, orientation, work visit, and organizational teaching. 3) Factors related to curriculum development. Work and demonstration of work and responsibility. 3.Their opinions on human resources development of local government organization is that there must be a clear development plan from the executive, field trip, to cultivate good conscience to staffs to be more responsible on their positives others insufficient budget on staffs development. Human resource development is critical to the development of this country. Implement religious guidelines for human resource development on a moral, ethical level. People will have the moral that is the key basis for developing knowledge, skills ie. If everyone has principles, morals, knowledge, they will be the potential key to the developing country.